Criminal Justice Contact, Racial Discrimination, and Health - Kilpatrick, Tanner (2018)
A sizeable body of research has shown that contact with the criminal justice system increases the risk for a variety of physical and mental health problems. However, less is known about mechanisms through which criminal justice contact increases the risk for health problems, particularly for women. This study extends research on criminal justice contact and health by examining the mediating role of racial discrimination. I hypothesized that racial discrimination would mediate the association between criminal justice contact (arrest, jail or prison) and mental health (depressive symptoms, overall mental health) and physical health (overall general health, doctor diagnosed health issues), and that the relationship among these variables would differ by gender. Using data on 613 African American adult caregivers from the Mobile Youth and Poverty Study (MYPS), I conducted a series of regression analyses to test these hypotheses. Results suggest that criminal justice contact increases the risk for depressive symptoms, poorer overall general health, and doctor diagnosed health issues among women, but not for men. Results further suggest that racial discrimination mediated the relationship between contact with the criminal justice system and depressive symptoms among women, but not overall general health or doctor diagnosed health issues. These findings lend support to theoretical perspectives and policies that aim to decrease discriminatory experiences and improve health among racial minority women following contact with the criminal justice system